Logger data at pond of polygon tundra in the Kolyma Delta near Pokhodsk (NE Siberia) sampled in 2012 - Schirrmeister, Lutz; Herzschuh, Ulrike; Pestryakova, Luidmila A; Wetterich, Sebastian; Frolova, Larisa A; Ushnitskaya, Lena A (In: Schirrmeister, L et al. (2023): Freshwater communities and environmental data of polygon tundra in the Kolyma Delta near Pokhodsk (NE Siberia) sampled in 2012 [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.951122, 2023)
Patterned ground of the polygonal tundra yields sensitive indicators of environmental and climate change. Polygon ponds, mires and cryosoils are typical components of Arctic Siberian wetlands underlain by permafrost. Field studies of recent environmental dynamics were carried out within the frame of the joint German-Russian DFG-RFBR project Polygons in tundra wetlands: state and dynamics under climate variability in Polar Regions (POLYGON) field studies were carried out in the Kolyma Delta in 2012 around the small fishing settlement Pokhodsk in summer 2012 and 2013. Using a multidisciplinary approach, several stages of polygonal systems were studied as modern tundra habitats . The floral and faunal associations of the polygonal tundra landscape were described. Ecological, hydrological, meteorological, limnological and cryological features were analyzed in order to evaluate modern environmental conditions and their essential controlling parameters. A monitoring program was carried out to measure changes of air, water and ground temperatures as well as water conductivity, water level and soil moisture and to collect water, diatom, zooplankton, and zoobenthos, samples. These data sets contain environmental field data, logger data, various ecological data, and analyses of sediments and water.
Keywords: air temperature; electrical conductivity; environmental data; ground temperature; hydrochemical parameters; hydrological data; sediment analysis; Soil Moisture; water temperature; Zooplankton